Prognostic value of the ALBI grade among patients with single hepatocellular carcinoma without macrovascular invasion. Issue 24 (18th June 2021) - Chen, Wenhao; Zhang, Zijian; Fang, Xianrui; Xiong, Li; Wen, Yu; Zhou, Jiangjiao; Kong, Fanhua; Zou, Heng
Abstract : Abstract: Although evidence for the application of an albumin-bilirubin (ALBI) grading system to assess liver function in hepatocellular carcinoma (HCC) is available, less is known whether it can be applied to determine the prognosis of single HCC with different tumor sizes. This study aimed to address this gap. Here, we enrolled patients who underwent hepatectomy due to single HCC from 2010 to 2014. Analyses were performed to test the potential of the ALBI grading system to monitor the long-term survival of single HCC subjects with varying tumor sizes. A total of 265 participants were recruited. The overall survival (OS) among patients whose tumors were ⩽7 cm was remarkably higher than those whose tumors were >7 cm. The Cox proportional hazards regression model identified the tumor differentiation grade, ALBI grade, and maximum tumor size as key determinants of OS. The ALBI grade could stratify the patients who had a single tumor ⩽7 cm into 2 distinct groups with different prognoses. The OS between ALBI grades 1 and 2 was comparable for patients who had a single tumor >7 cm. We showed that the ALBI grading system can predict disease outcomes in patients with a single HCC with a tumor size ⩽7 cm. However, the ALBI grade may not predict the prognosis of patients with a single tumor >7 cm.